Structural dynamics of the box C/D RNA kink-turn and its complex with proteins: the role of the A-minor 0 interaction, long-residency water bridges, and structural ion-binding sites revealed by molecular simulations - Spacková, Nad'a; Réblová, Kamila; Sponer, Jirí (The journal of physical chemistry. B, 2010)
Kink-turns (K-turns) are recurrent elbow-like RNA motifs that participate in protein-assisted RNA folding and contribute to RNA dynamics. We carried out a set of molecular dynamics (MD) simulations using parm99 and parmbsc0 force fields to investigate structural dynamics of the box C/D RNA and its complexes with two proteins: native archaeal L7ae protein and human 15.5 kDa protein, originally bound to very similar structure of U4 snRNA. The box C/D RNA forms K-turn with A-minor 0 tertiary interaction between its canonical (C) and noncanonical (NC) stems. The local K-turn architecture is thus different from the previously studied ribosomal K-turns 38 and 42 having A-minor I interaction. The simulations reveal visible structural dynamics of this tertiary interaction involving altogether six substates which substantially contribute to the elbow-like flexibility of the K-turn. The interaction can even temporarily shift to the A-minor I type pattern; however, this is associated with distortion of the G/A base pair in the NC-stem of the K-turn. The simulations show reduction of the K-turn flexibility upon protein binding. The protein interacts with the apex of the K-turn and with the NC-stem. The protein-RNA interface includes long-residency hydration sites. We have also found long-residency hydration sites and major ion-binding sites associated with the K-turn itself. The overall topology of the K-turn remains stable in all simulations. However, in simulations of free K-turn, we observed instability of the key C16(O2')-A7(N1) H-bond, which is a signature interaction of K-turns and which was visibly more stable in simulations of K-turns possessing A-minor I interaction. It may reflect either some imbalance of the force field or it may be a correct indication of early stages of unfolding since this K-turn requires protein binding for its stabilization. Interestingly, the 16(O2')-7(N1) H- bond is usually not fully lost since it is replaced by a water bridge with a tightly bound water, which is adenine-specific similarly as the original interaction. The 16(O2')-7(N1) H-bond is stabilized by protein binding. The stabilizing effect is more visible with the human 15.5 kDa protein, which is attributed to valine to arginine substitution in the binding site. The behavior of the A-minor interaction is force-field-dependent because the parmbsc0 force field attenuates the A-minor fluctuations compared to parm99 simulations. Behavior of other regions of the box C/D RNA is not sensitive to the force field choice. Simulation with net-neutralizing Na(+) and 0.2 M excess salt conditions appear in all aspects equivalent. The simulations show loss of a hairpin tetraloop, which is not part of the K-turn. This was attributed to force field limitations.
Keywords: molekulární modely; voda; Models, Molecular; Molecular Dynamics Simulation; konformace nukleové kyseliny; ionty; simulace molekulární dynamiky; Nucleic Acid Conformation; lidé; Ions; vodíková vazba; RNA; archeální RNA; Hydrogen Bonding; RNA, Archaeal; Humans; Water